Equilibrium Airfares, Frequencies and Airport Taxes in a Multiple Airport Region: An Application of the Nested Logit Demand Model - Eric Pels; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 1998)
In this paper a model, based on the nested multinomial logit model, is used to analyze airport competition and airline competition in a multiple airport region. It is shown that if the frequency elasticity of demand is smaller than 1, airfare-frequency and airport tax equilibria exist and are unique.Symmetric equilibria are derived analytically and their properties are discussed. Asymmetric equilibria are obtained numerically, and their properties are discussed.
Keywords: 330; Luftverkehr; Verkehrstarif; Steuer; Theorie